Boron and boron isotope systematics in the peralkaline Ilímaussaq intrusion (South Greenland) and its granitic country rocks: a record of magmatic and hydrothermal processes - Kaliwoda, Melanie; Marschall, Horst R.; Marks, Michael A. W.; Ludwig, Thomas; Altherr, Rainer; Markl, Gregor (Lithos, 2011)
Concentrations of boron in whole rocks and minerals of the peralkaline, 1.16Ga Ilímaussaq intrusion and its granitic country rocks (South Greenland) were analysed using secondary ion mass spectrometry (SIMS) and prompt gamma neutron activation (PGNAA) analysis. The intrusion consists of an early augite-syenite shell, a later alkali-granite sheet and still later nepheline syenites, which dominate the Complex. Boron concentrations are high (250-280μg/g) in all rocks containing fresh sodalite, whereas boron is constantly low in the sodalite-free augite syenites (4-6μg/g) and in the alkali granites (7-22μg/g). Rocks with sodalite altered to analcime contain only low amounts of boron (2-7μg/g), which records boron extraction by late-magmatic fluids. Concentration profiles of B in the analysed minerals (olivine, amphibole, clinopyroxene, aenigmatite, eudialyte, biotite, feldspar, nepheline and sodalite) record magmatic fractionation to various extents, late-magmatic to hydrothermal fluid/rock interaction, and sub-solidus diffusion. Whole-rock concentration data cannot be directly translated into the geochemical evolution of the peralkaline melts, since they are largely affected by cumulate fractionation of sodalite and amphibole and furthermore by late-stage hydrothermal alteration processes resulting in B loss. However, trace-element concentrations of mineral zones representing equilibrium fractionation from magmatic liquids can be used in combination with mineral-melt partition coefficients to unravel the enrichment processes of elements in the melt. Boron isotope values of minerals from the intrusion and the country rocks resemble the trend observed for Li isotopes in an earlier study. Amphibole and feldspar display a clear trend from light boron in the inner nepheline syenitic part of the intrusion (δ11B=−20‰ and −17‰ for amphibole and feldspar, respectively) through intermediate values in the outer augite syenites (δ11B=−10‰ and −6‰ for amphibole and feldspar, respectively) to heavy boron with δ11B=+2‰ for amphibole and +4‰ for feldspar in the country rock granites close to the contact with the intrusion. The values are interpreted to reflect the entry of meteoric fluids with heavy B along the intrusive contact.
Gesehen am 07.07.2022